2012
DOI: 10.1002/cncr.27758
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of linifanib (ABT‐869) in patients with unresectable or metastatic hepatocellular carcinoma

Abstract: BACKGROUND: The efficacy and safety of linifanib (ABT‐869), a selective inhibitor of vascular endothelial growth factor and platelet‐derived growth factor receptor tyrosine kinases, were assessed in this phase 2, single‐arm, open‐label, multicenter trial. METHODS: Eligible patients had unresectable or metastatic hepatocellular carcinoma and had received ≤ 1 prior systemic therapy. Patients received oral linifanib at a fasting dose of 0.25 mg/kg,. The primary endpoint was the progression‐free rate at 16 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…Linifanib (ABT-869), a multitargeted tyrosine kinase inhibitor, inhibits the members of the VEGFR and PDGFR families [34] . Linifanib as single agent showed clinical antitumor activity in OS (9.7 mo) and TTP (3.7 mo) [35] . ABT-869 appeared to benefit HCC patients, with an acceptable safety profile.…”
Section: Other Antiangiogenic Therapiesmentioning
confidence: 99%
“…Linifanib (ABT-869), a multitargeted tyrosine kinase inhibitor, inhibits the members of the VEGFR and PDGFR families [34] . Linifanib as single agent showed clinical antitumor activity in OS (9.7 mo) and TTP (3.7 mo) [35] . ABT-869 appeared to benefit HCC patients, with an acceptable safety profile.…”
Section: Other Antiangiogenic Therapiesmentioning
confidence: 99%
“…Interim Phase II results in patients with advanced HCC showed a median TTP of 3.7 months with ABT-869 treatment and a safety profile consistent with angiogenesis inhibition. In the Toh et al study, the authors demonstrate that linifanib as a single agent was found to be clinically active in patients with advanced HCC, with an acceptable safety profile [48].…”
Section: Other Agentsmentioning
confidence: 98%
“…Linifanib[ABT-869] is a multitargeted tyrosine kinase inhibitor that inhibits multiple members of the VEGFR and PDGFR families [48]. In a xenograft model of HCC, ABT-869 significantly reduced tumor burden.…”
Section: Other Agentsmentioning
confidence: 99%
“…Linifanib is a dual TKI for VEGFR and PDGFR.In a phase II trial, the results were as follows: median PFS, 3.7 months; median OS, 9.7 months [23]. In the LIGHT phase III trial of linifanib as a first-line drug, the median OS was 9.1 months with linifanib and 9.8 months with sorafenib (HR 1.05, 95 % CI 0.90-1.22, NS), which indicated that linifanib was neither superior nor inferior to sorafenib [24].…”
Section: Linifanibmentioning
confidence: 99%